2018
DOI: 10.4049/jimmunol.1701271
|View full text |Cite
|
Sign up to set email alerts
|

Passive Serum Therapy to Immunomodulation by IVIG: A Fascinating Journey of Antibodies

Abstract: The immunoregulatory and anti-infective properties of normal circulating polyclonal Abs have been exploited for the therapeutic purposes in the form of IVIG as well as several hyperimmune globulins. Current knowledge on the therapeutic use of normal Igs is based on the discoveries made by several pioneers of the field. In this paper, we review the evolution of IVIG over the years. More importantly, the process started as an s.c. replacement in γ globulin-deficient patients, underwent metamorphosis into i.m. Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 97 publications
0
20
0
Order By: Relevance
“…The emerging evidence suggests that IVIG targets various arms of the immune system, culminating in inhibition of inflammatory cells and soluble mediators while reciprocally enhancing immune regulatory cells and their functions. Several mechanisms of action for IVIG have been proposed since its first successful therapeutic use in ITP [3]. It was thought initially that IVIG exerts a beneficial effect in autoimmune disease patients via saturation/blockade of Fc receptors on phagocytes such as monocytes and macrophages and reduces the immune complex-mediated activation of these innate cells [59,66].…”
Section: Natural Igg (Nigg): Role Of Nabs In Immune Tolerance/homeostmentioning
confidence: 99%
See 1 more Smart Citation
“…The emerging evidence suggests that IVIG targets various arms of the immune system, culminating in inhibition of inflammatory cells and soluble mediators while reciprocally enhancing immune regulatory cells and their functions. Several mechanisms of action for IVIG have been proposed since its first successful therapeutic use in ITP [3]. It was thought initially that IVIG exerts a beneficial effect in autoimmune disease patients via saturation/blockade of Fc receptors on phagocytes such as monocytes and macrophages and reduces the immune complex-mediated activation of these innate cells [59,66].…”
Section: Natural Igg (Nigg): Role Of Nabs In Immune Tolerance/homeostmentioning
confidence: 99%
“…There was a parallel expansion in the application of serum with anti-infection capabilities against other microbial diseases to confer immunity against dreadful pathogens, hence the name immunoglobulins (Igs) came into practice. Subsequently, thorough characterization of the antibodies produced following microbial infection or immunization, referred to as immune antibodies, was done [3]. Further studies identified varieties of Igs differing in their structure and function.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, IVIG exhibits an immense repertoire of antibodies with specificities toward a magnitude of antigens (1). Its inherent polyspecificity may provide the basis of its pluripotent anti-inflammatory effects if used as a high-dose therapy (2), whereby a broad range of different mechanisms may act in concert, also depending on the pathogenesis of the targeted disease (3)(4)(5). Accordingly, IVIG is successfully used for the treatment of a broad range of heterogenous diseases, including neutrophil-associated disorders such as Kawasaki disease, an acute febrile vasculitis syndrome (6).…”
Section: Introductionmentioning
confidence: 99%
“…Intravenous immunoglobulin (IVIG) is in use for numerous clinically approved pathological conditions (Hässig, 1967 ; Stiehm et al, 2008 ), and in more than 100 different indications as an off-label drug (João et al, 2018 ). The rationale to apply IVIG to patients with CDI is based on the prevalence of serum antibodies against TcdA and TcdB in healthy blood donors (Viscidi et al, 1983 ; Bacon and Fekety, 1994 ), and a low antitoxin serum level in patients that are predisposed for recurrent, prolonged or severe CDI (Salcedo et al, 1997 ; Kyne et al, 2000 ; Table 1 ).…”
Section: Antibodies For Systemic Administration To Prevent (Relapsingmentioning
confidence: 99%